Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

By using supercritical peeling graphene and surface modification additives for ball milling, a carbon cladding layer is formed, which solves the performance problems caused by volume changes in the silicon-based negative electrode material during charging and discharging, and achieves better conductivity and battery performance.

CN119601609APending Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311160379.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The volume of the silicon-based negative electrode material changes greatly during the charging and discharging process, resulting in particle rupture, active substances falling off and repeated formation of solid electrolyte membranes, resulting in poor battery circulation performance and low Coulomb efficiency.

Method used

The graphene obtained from supercritical peeling and surface modification additives are ball milled to form a carbon cladding layer, enhance the electronic conductivity of the silicon-based particles, and carbon cladding is achieved through spray drying and calcining steps.

Benefits of technology

It improves the conductivity of silicon-based particles, enhances the cycle performance and coulomb efficiency of the battery, and is simple in preparation, environmentally friendly raw materials, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601609A_ABST
    Figure CN119601609A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode plate and a lithium ion battery. The method comprises the following steps that S1, supercritical exfoliated graphene and a surface modification additive make contact with a first organic phase, first ball milling treatment is carried out, a first product is obtained, and the surface modification additive is selected from one or more of a surfactant and a high polymer material; s2, enabling the first product, a silicon-containing substrate and a second organic phase to be in contact, and performing second ball milling treatment to obtain a second product; s3, performing spray drying treatment on the second product to obtain a third product; and S4, carrying out roasting treatment on the third product. The method can improve the electronic conductivity among the silicon-based particles, and is simple to operate and easy to implement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of lithium-ion batteries, and in particular to a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a lithium-ion battery. Background Art

[0002] When silicon-based negative electrode materials are used in lithium-ion batteries, the theoretical specific capacity is greater than 4000mAh / g, and the lithium insertion potential is higher than that of graphite, which means that the possibility of lithium precipitation is low, and therefore the safety is high. In addition, the particle size of silicon-containing negative electrodes can be smaller, and the fast charging capability is good. However, the disadvantage of silicon-based negative electrodes is that during the charging and discharging process, the generation and decomposition of silicon-lithium alloys are accompanied by huge volume changes, up to 300%. This causes the rupture of silicon-based particles, the shedding of active materials on the pole pieces, and the repeated formation of SEI (solid electrolyte membrane) films, and ultimately the battery performance is manifested as poor cycle performance and low coulombic efficiency.

[0003] CN111816859A discloses a silicon-based negative electrode material with a core of silicon, silicon oxide and silicate and a carbon film on the surface of the core, wherein the carbon layer is amorphous carbon with a thickness between 50nm and 200nm. CN111162268A discloses that the carbon layer is formed by chemical vapor deposition, and the reaction gas includes carbon source gases such as methane, acetylene, ethylene, propyne, propylene and a certain proportion of hydrogen. CN113725409A discloses a silicon-based negative electrode material with a carbon nanotube coated on the surface of a silicon-based particle, and a carbon layer coated on the surface of the silicon-based particle and the carbon nanotube. The carbon coating method is gas phase carbon coating or liquid phase carbon coating. The carbon source of the liquid phase carbon coating is selected from at least one of polyaniline, polypyrrole, polythiophene, polyacrylonitrile or their copolymers or asphalt and glucose. CN113611858A uses hydrochloric acid as a reaction aid to coat pyrrole, aniline and dopamine on the surface of porous silicon-based particles under liquid phase conditions, and then achieves carbon coating. CN114914418A discloses a silicon nanocomposite negative electrode material coated with redox graphene. CN115064666A discloses a polyaniline grafted graphene oxide coated silicon negative electrode material. CN114613955A discloses a silicon negative electrode material in which sulfonated graphene is coated on the surface of an amino-treated nano silicon source.

[0004] The above patents introduce two situations of carbon coating of silicon-based particles: one is to coat a layer of amorphous carbon on the surface by gas phase, liquid phase, and solid phase without using graphene; the other is to use graphene oxide for surface bonding to achieve carbon coating. High-temperature thermal cracking is more effective in achieving amorphous carbon coating, but the thickness control is more difficult, and the temperature is high, which is prone to produce environmentally unfriendly cracking tail gas. In the method of using graphene oxide, graphene oxide itself contains oxygen-containing groups, has poor conductivity, and needs to be reduced, which is a more cumbersome operation. Summary of the invention

[0005] The purpose of the present disclosure is to provide a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode plate and a lithium-ion battery, so as to improve the electronic conductivity between silicon-based particles, and the operation is simple and easy to implement.

[0006] In order to achieve the above object, the present disclosure provides a method for preparing a silicon-carbon negative electrode material in a first aspect, comprising the following steps:

[0007] S1, contacting the supercritically exfoliated graphene and the surface modification additive with a first organic phase, and performing a first ball milling treatment to obtain a first product, wherein the surface modification additive is selected from one or more of a surfactant and a polymer material;

[0008] S2, contacting the first product, the silicon-containing matrix and a second organic phase, and performing a second ball milling treatment to obtain a second product;

[0009] S3, spray drying the second product to obtain a third product;

[0010] S4, calcining the third product.

[0011] Optionally, in step S1, the weight ratio of the graphene to the surface modification additive is 1:0.01-0.5, preferably 1:0.01-0.3; preferably, in the surface modification additive, the weight ratio of the surfactant to the polymer material is 0.1-10:1, preferably 0.1-1:1;

[0012] Optionally, in step S1, the planar size of the supercritically exfoliated graphene is in the range of 2 to 10 μm; preferably, based on the total weight of the supercritically exfoliated graphene, more than 80% by weight of the supercritically exfoliated graphene has less than 10 layers; the heteroatom content of the supercritically exfoliated graphene is less than 1% by weight, and the heteroatom is selected from one or more of oxygen, nitrogen and sulfur;

[0013] Optionally, the supercritically exfoliated graphene is prepared by a method comprising the following steps:

[0014] At a temperature of 32°C to 150°C and a pressure of more than 4MPa, a gaseous intercalation medium is used to exfoliate graphite sheets in a reaction vessel under a supercritical state, and the exfoliated powder is collected to obtain supercritically exfoliated graphene; optionally, the gaseous intercalation medium is selected from one or both of carbon dioxide and nitrogen; optionally, the reaction vessel is a stirred tank or a reactor.

[0015] Optionally, the surfactant is selected from one or more of sodium lignin sulfonate, sodium methylene dibenzene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, polyol esters, fatty acid glycerides, oleic acid, oleylamine, oleamide, stearic acid, polysorbate-80, polyethylene glycol octylphenyl ether and cetyltrimethylammonium bromide; preferably, the surfactant is selected from one or more of sodium lignin sulfonate, polyol esters, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, oleamide and stearic acid;

[0016] The polymer material is selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid, polyurethane, polyphenylene sulfide, polystyrene butadiene copolymer, epoxy resin, acrylonitrile butadiene styrene, polyvinyl pyrrolidone, polycarbonate and polyamide; preferably, the polymer material is selected from one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, polyacrylic acid, polystyrene butadiene copolymer and polyamide; optionally, the molecular weight of the polymer material is (0.01-20)×10 5 ;

[0017] Optionally, the first organic phase is selected from one or more of nitrogen methyl pyrrolidone, ethanol, isopropanol, cyclohexane, petroleum ether, furfural, tetrahydrofuran, high aromatic oil and paraffin mineral oil;

[0018] Preferably, the amount of the first organic phase used is 10 to 200 ml, preferably 50 to 100 ml, relative to 1 g of graphene.

[0019] Optionally, the conditions of the first ball milling treatment include: a ball milling temperature of 23 to 60°C, a ball milling speed of 200 to 1000 rpm, a ball milling time of 0.5 to 12 hours, and a ball-to-material ratio of 1 to 40:1; preferably, the ball milling temperature is 30 to 50°C, the ball milling speed is 300 to 800 rpm, the ball milling time is 2 to 6 hours, and the ball-to-material ratio is 5 to 20:1.

[0020] Optionally, step S1 includes:

[0021] The graphene is dispersed in the first organic phase and ball-milled under the first ball-milling condition to obtain a first ball-milling product; the first ball-milling product is then contacted with the surfactant and ball-milled under the second ball-milling condition to obtain a second ball-milling product; the second ball-milling product is contacted with a polymer material and ball-milled under the third ball-milling condition to obtain a third ball-milling product; the third ball-milling product is subjected to a first ultrasonic dispersion treatment and ball-milled under the fourth ball-milling condition to obtain the first product;

[0022] Optionally, the conditions for the first ultrasonic dispersion treatment include: sealed and constant-temperature ultrasonic treatment, with an ultrasonic time of 3 to 8 h, an ultrasonic power of 600 to 3000 W, and an ultrasonic frequency of 20 to 40 KHz; preferably, the ultrasonic time is 3 to 7 h, the ultrasonic power is 600 to 1500 W, and the ultrasonic frequency is 30 to 40 KHz.

[0023] Optionally, each of the first ball milling conditions, the second ball milling conditions, the third ball milling conditions, and the fourth ball milling conditions independently includes: a ball milling temperature of 23 to 60 °C, a ball milling rotation speed of 200 to 1000 rpm, a ball milling time of 0.5 to 12 h, and a ball-to-material ratio of 1 to 40:1; preferably, the ball milling temperature is 30 to 50 °C, the ball milling rotation speed is 300 to 800 rpm, the ball milling time is 2 to 6 h, and the ball-to-material ratio is 5 to 20:1.

[0024] Optionally, in step S2, the silicon-containing matrix is selected from one or more of nano-silicon, SiOx, and a nano-silicon-metal M alloy, where 0.3 < x < 1.6, and M is selected from one or more of aluminum, iron, copper, titanium, niobium, chromium, lithium, manganese, nickel, cobalt, tin, vanadium, germanium, magnesium, calcium, molybdenum, and lanthanum. Optionally, based on the total weight of the nano-silicon-metal M alloy, the silicon content is 70 to 99% by weight, preferably 80 to 98% by weight.

[0025] Preferably, the weight ratio of the silicon-containing matrix to the supercritically exfoliated graphene is 1 to 20:1, preferably 5 to 20:1.

[0026] Optionally, the second organic phase is selected from one or more of N-methylpyrrolidone, ethanol, isopropanol, cyclohexane, petroleum ether, furfural, tetrahydrofuran, high-aromatic hydrocarbon oil, and paraffin mineral oil.

[0027] Preferably, with respect to 1 g of the solid of the first product, the amount of the second organic phase used is 10 to 200 ml, preferably 50 to 100 ml.

[0028] Optionally, in step S2, the conditions for the second ball milling treatment include: a ball milling temperature of 23 to 60 °C, a ball milling rotation speed of 50 to 600 rpm, a ball milling time of 0.5 to 12 h, and a ball-to-material ratio of 1 to 40:1; preferably, the ball milling temperature is 30 to 50 °C, the ball milling rotation speed is 250 to 400 rpm, the ball milling time is 2 to 6 h, and the ball-to-material ratio is 5 to 20:1.

[0029] Optionally, step S2 includes:

[0030] The first product is contacted with a silicon-containing matrix, ball-milled under the fifth ball-milling condition, and a second organic phase is added to obtain a fourth ball-milled product; the fourth ball-milled product is subjected to a second ultrasonic dispersion treatment; after the second ultrasonic dispersion treatment is completed, the ball-milling is continued under the sixth ball-milling condition to obtain a suspension of the second product and to perform the spray drying treatment;

[0031] Optionally, the conditions of the second ultrasonic dispersion treatment include: closed constant temperature ultrasound, ultrasound time of 3 to 8 hours, ultrasound power of 600 to 3000 W, and ultrasound frequency of 20 to 40 KHz; preferably, ultrasound time of 4 to 7 hours, ultrasound power of 600 to 1500 W, and ultrasound frequency of 30 to 40 KHz;

[0032] Optionally, the fifth ball milling condition and the sixth ball milling condition independently include: the ball milling temperature is 23-60°C, the ball milling speed is 50-600rpm, the ball milling time is 0.5-12h, and the ball-to-material ratio is 1-40:1; preferably, the ball milling temperature is 30-50°C, the ball milling speed is 250-400rpm, the ball milling time is 2-6h, and the ball-to-material ratio is 5-20:1.

[0033] Optionally, in step S3, the conditions for the spray drying treatment include: a feed temperature of 120 to 200°C, an outlet temperature of 80 to 100°C, a carrier gas flow rate of 12 to 20 L / min, an inlet pressure of 0.3 to 0.8 MPa, and the carrier gas is selected from one or more of nitrogen and argon; preferably, the feed temperature is 140 to 190°C, the outlet temperature is 90 to 100°C, the carrier gas flow rate is 14 to 18 L / min, and the inlet pressure is 0.4 to 0.6 MPa.

[0034] Optionally, in step S4, the conditions for the calcination treatment include: in an inert gas atmosphere, first heating to 270-700° C., and then keeping warm for 1-12 hours; preferably, first heating to 500-700° C., and then keeping warm for 3-6 hours; preferably, the heating rate is 0.5-5° C. / min, preferably 0.5-3° C. / min;

[0035] Optionally, the inert atmosphere is selected from one or more of nitrogen and argon.

[0036] Optionally, the method further comprises: using the product obtained by the calcination treatment as the silicon-containing matrix, and repeating steps S2 to S4 to obtain a calcined product having a plurality of carbon coating layers; preferably, the steps are repeated 2 to 3 times.

[0037] A second aspect of the present disclosure provides a silicon-carbon negative electrode material prepared according to the method described in the first aspect of the present disclosure.

[0038] Optionally, the silicon-carbon negative electrode material comprises a silicon-containing matrix and a carbon coating layer, and the carbon coating layer comprises graphene; optionally, the content of the carbon coating layer is 4 to 49% by weight, preferably 5 to 20% by weight;

[0039] Optionally, the total thickness of the carbon coating layer is 10 to 200 nm, preferably 50 to 100 nm;

[0040] Optionally, the D of the silicon-carbon negative electrode material 50 The particle size is 2-28 μm, and the BET specific surface area is 1-50 m 2 / g; Preferably, the D of the silicon-carbon negative electrode material 50 The particle size is 4 to 18 μm, and the BET specific surface area is 1 to 10 m 2 / g.

[0041] A third aspect of the present disclosure provides a negative electrode plate, comprising the silicon-carbon negative electrode material described in the second aspect of the present disclosure.

[0042] Optionally, the negative electrode plate is prepared by a method comprising the following steps:

[0043] The silicon-carbon negative electrode material is made into a negative electrode slurry, which is then coated on the surface of the negative electrode current collector, and dried to obtain a negative electrode sheet;

[0044] Preferably, the negative electrode slurry comprises the silicon-carbon negative electrode material, a conductive agent, a thickener, a binder and water;

[0045] Further preferably, based on the total weight of solids in the negative electrode slurry, the content of the silicon-carbon negative electrode material is 80-96 weight %, the content of the conductive agent is 0.01-5 weight %, the content of the thickener is 1-10 weight %, and the content of the binder is 1-10 weight %; optionally, the weight ratio of the total weight of solids in the negative electrode slurry to water is 2-0.5:1;

[0046] Optionally, the conductive agent is selected from one or more of conductive carbon black, acetylene black, Ketjen black, single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon nanofibers;

[0047] The thickener is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium alginate, aqueous polyurethane, polyvinyl alcohol, chitosan and β-cyclodextrin;

[0048] The binder is selected from one or more of styrene butadiene copolymer, polyacrylic acid, sodium polyacrylate, polyimide, polyvinylidene fluoride, nitrile rubber, butadiene rubber, xanthan gum and gum arabic.

[0049] A fourth aspect of the present disclosure provides a lithium-ion battery, which includes a positive electrode plate, a negative electrode plate as described in the third aspect of the present disclosure, a battery separator, and an electrolyte.

[0050] Through the above technical scheme, the present disclosure provides a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode plate and a lithium-ion battery. The graphene obtained by supercritical exfoliation adopted in the present disclosure has a green and environmentally friendly production process, large output, low cost and few defects; the graphene obtained by supercritical exfoliation that is basically free of heteroatoms adopted in the present disclosure has better conductivity, and it is used to coat silicon-based particles to enhance the conductivity of silicon-based particles; the coating temperature is low, and carbon coating can be achieved without high-temperature carbonization, and there is very little cracking tail gas; the coating thickness can also be controlled. The graphene coated on the surface of the silicon-based particles can not only be used as a conductive agent, but also as a high-capacity active material to participate in the insertion and extraction of lithium ions. In the preparation process of the present disclosure, the supercritically exfoliated graphene and the surface modification additive are first ball-milled, which is beneficial to improve the dispersion performance of the graphene and improve the uniformity of the subsequent carbon coating. The preparation process of the negative electrode material provided by the present disclosure is simple, the raw materials are green and environmentally friendly, and it is suitable for industrial production and application.

[0051] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0053] Figure 1 A transmission electron microscope image of graphene obtained by supercritical exfoliation provided in Example 1 of the present disclosure;

[0054] Figure 2 A nitrogen adsorption / desorption curve diagram of graphene obtained by supercritical exfoliation provided in Example 1 of the present disclosure;

[0055] Figure 3 The battery cycle performance diagram of the negative electrode materials obtained in Example 1 and Comparative Example 3;

[0056] Figure 4 The battery cycle performance diagram of the negative electrode materials obtained in Example 1 and Example 3;

[0057] Figure 5 The battery cycle performance diagram of the negative electrode materials obtained in Example 2 and Comparative Example 2. DETAILED DESCRIPTION

[0058] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0059] The first aspect of the present disclosure provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0060] S1, contacting the supercritically exfoliated graphene and the surface modification additive with a first organic phase, and performing a first ball milling treatment to obtain a first product, wherein the surface modification additive is selected from one or more of a surfactant and a polymer material;

[0061] S2, contacting the first product, the silicon-containing matrix and a second organic phase, and performing a second ball milling treatment to obtain a second product;

[0062] S3, spray drying the second product to obtain a third product;

[0063] S4, calcining the third product.

[0064] The present disclosure provides a method for preparing silicon-carbon negative electrode materials. The graphene obtained by supercritical exfoliation adopted in the present disclosure has a green and environmentally friendly production process, large output, low cost, and few defects; the graphene obtained by supercritical exfoliation adopted in the present disclosure substantially free of heteroatoms has better conductivity, and the graphene is used to coat silicon-based particles to enhance the conductivity of silicon-based particles; the coating temperature is low, and carbon coating can be achieved without high-temperature carbonization, and there is little cracking tail gas. The graphene coated on the surface of the silicon-based particles can not only serve as a conductive agent, but also as a high-capacity active material to participate in the insertion and extraction of lithium ions. The preparation process of the negative electrode material provided by the present disclosure is simple, the raw materials are green and environmentally friendly, and it is suitable for industrial production and application.

[0065] In one embodiment, in step S1, the weight ratio of the graphene to the surface modification additive is 1:0.01 to 0.5, preferably 1:0.01 to 0.3. Adding graphene and the surface modification additive according to the optimized weight ratio in this embodiment is conducive to improving the performance of the final silicon-carbon negative electrode material.

[0066] In a specific embodiment, in the surface modification additive, the weight ratio of the surfactant to the polymer material is 0.1 to 10: 1, preferably 0.1 to 1: 1. Adding the surfactant and the polymer material according to the optimized weight ratio in this embodiment can further enhance the interaction with the supercritically exfoliated graphene and improve the dispersion uniformity.

[0067] In one embodiment, in step S1, the plane size of the supercritically exfoliated graphene is in the range of 2 to 10 μm; preferably, based on the total weight of the supercritically exfoliated graphene, more than 80% by weight of the supercritically exfoliated graphene has less than 10 layers; the heteroatom content of the supercritically exfoliated graphene is less than 1% by weight, and the heteroatom is selected from one or more of oxygen, nitrogen and sulfur. The plane size of graphene refers to the size of the graphene sheet obtained by supercritical exfoliation in the plane dimension, which is in the range of 2 to 10 μm.

[0068] In a specific embodiment, the supercritically exfoliated graphene is prepared by a method comprising the following steps:

[0069] At a temperature of 32°C to 150°C and high pressure (≥4MPa), using gaseous intercalation media such as carbon dioxide and nitrogen in a supercritical state, in a stirring tank or a reactor, the graphite sheets are exfoliated, and the exfoliated powder is collected to obtain graphene materials. The size of graphene prepared by supercritical exfoliation is 2 to 10μm, and more than 80% of the graphene is less than 10 layers thick.

[0070] In one embodiment, the surfactant is selected from one or more of sodium lignin sulfonate, sodium methylene dibenzene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, polyol esters, fatty acid glycerides, oleic acid, oleylamine, oleamide, stearic acid, polysorbate-80 (Tween-80, Tween-80), polyethylene glycol octylphenyl ether (Triton X-100, Triton X-100) and cetyltrimethylammonium bromide; preferably, the surfactant is selected from one or more of sodium lignin sulfonate, polyol esters, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, oleamide and stearic acid;

[0071] The polymer material is selected from one or more of poly(vinylidene fluoride), carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid, polyurethane, polyphenylene sulfide, polystyrene butadiene copolymer, epoxy resin, acrylonitrile butadiene styrene, polyvinyl pyrrolidone, polycarbonate and polyamide; preferably, the polymer material is selected from one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, polyacrylic acid, polystyrene butadiene copolymer and polyamide. In the present disclosure, the surfactant and polymer material can be purchased through ordinary commercial channels or prepared by known methods. Preferably, the molecular weight of the polymer material is 0.1×10 4 ~10×10 5 , preferably 0.5×10 4 ~5×10 5 .

[0072] In one embodiment, in step S1, the conditions of the first ball milling treatment include: a ball milling temperature of 23 to 60°C, a ball milling speed of 200 to 1000 rpm, a ball milling time of 0.5 to 12 hours, and a ball-to-material ratio of 1 to 40:1; preferably, the ball milling temperature is 30 to 50°C, the ball milling speed is 300 to 800 rpm, the ball milling time is 2 to 6 hours, and the ball-to-material ratio is 5 to 20:1.

[0073] In a specific embodiment, the first organic phase is selected from one or more of nitrogen methyl pyrrolidone, ethanol, isopropanol, cyclohexane, petroleum ether, furfural, tetrahydrofuran, high aromatic oil and paraffin mineral oil; wherein high aromatic oil refers to hydrocarbon oil with an aromatic content of 45% by weight or more;

[0074] Preferably, the amount of the first organic phase used is 10 to 200 ml, preferably 50 to 100 ml, relative to 1 g of graphene.

[0075] In the present disclosure, the surfactant and the polymer material can be added simultaneously or sequentially. For example, the surfactant is added first, ball milled for a period of time, and then the polymer material is added to continue ball milling. The conditions for ball milling in the order of sequence are the same as the conditions for the first ball milling. The conditions for ball milling after adding the surfactant and for ball milling after adding the polymer material can be the same or different, and are preferably the same.

[0076] In a specific implementation, step S1 includes:

[0077] The graphene is dispersed in the first organic phase and ball-milled under the first ball-milling condition to obtain a first ball-milling product; the first ball-milling product is then contacted with the surfactant and ball-milled under the second ball-milling condition to obtain a second ball-milling product; the second ball-milling product is contacted with a polymer material and ball-milled under the third ball-milling condition to obtain a third ball-milling product; the third ball-milling product is subjected to a first ultrasonic dispersion treatment and then ball-milled under the fourth ball-milling condition to obtain the first product. The present invention pre-disperses the graphene by the first ultrasonic dispersion treatment, which is helpful for the dispersion and stabilization of the graphene in the organic phase.

[0078] In a specific embodiment, the conditions of the first ultrasonic dispersion treatment include: closed constant temperature ultrasound, ultrasonic time of 3 to 8 hours, ultrasonic power of 600 to 3000 W, and ultrasonic frequency of 20 to 40 KHz; preferably, ultrasonic time of 3 to 7 hours, ultrasonic power of 600 to 1500 W, and ultrasonic frequency of 30 to 40 KHz. Dispersion or ball milling according to the optimized conditions in this embodiment can improve the coating effect of graphene, thereby improving the performance of silicon-carbon negative electrode materials.

[0079] In a specific embodiment, the first ball milling condition, the second ball milling condition, the third ball milling condition, and the fourth ball milling condition each independently include: the ball milling temperature is 23 to 60 °C, the ball milling speed is 200 to 1000 rpm, the ball milling time is 0.5 to 12 h, and the ball-to-material ratio is 1 to 40:1; preferably, the ball milling temperature is 30 to 50 °C, the ball milling speed is 300 to 800 rpm, the ball milling time is 2 to 6 h, and the ball-to-material ratio is 5 to 20:1.

[0080] In an embodiment, the silicon-containing matrix is selected from one or more of nano-silicon, SiOx, and nano-silicon-metal M alloy, where 0.3 < x < 1.6, and M is selected from one or more of aluminum, iron, copper, titanium, niobium, chromium, lithium, manganese, nickel, cobalt, tin, vanadium, germanium, magnesium, calcium, molybdenum, and lanthanum. Optionally, based on the total weight of the nano-silicon-metal M alloy, the silicon content is 70 to 99% by weight, preferably 80 to 98% by weight.

[0081] In a specific embodiment, the D of the nano-silicon 50 particle size is 50 to 200 nm; the D of SiOx 50 particle size is 0.5 μm to 9 μm; the D of the nano-silicon-metal M alloy 50 particle size is 10 nm to 1000 nm.

[0082] In a preferred embodiment, the weight ratio of the silicon-containing matrix to the supercritically exfoliated graphene is 1 to 20:1, preferably 5 to 20:1.

[0083] In a specific embodiment, the second organic phase is selected from one or more of N-methylpyrrolidone, ethanol, isopropanol, cyclohexane, petroleum ether, furfural, tetrahydrofuran, high-aromatic oil, and paraffin mineral oil;

[0084] Preferably, relative to 1 g of the solid of the first product, the amount of the second organic phase used is 10 to 200 ml, preferably 50 to 100 ml.

[0085] In an embodiment, in step S2, the conditions for the second ball milling treatment include: the ball milling temperature is 23 to 60 °C, the ball milling speed is 50 to 600 rpm, the ball milling time is 0.5 to 12 h, and the ball-to-material ratio is 1 to 40:1; preferably, the ball milling temperature is 30 to 50 °C, the ball milling speed is 250 to 400 rpm, the ball milling time is 2 to 6 h, and the ball-to-material ratio is 5 to 20:1. In the present disclosure, the first product and the silicon-containing matrix are subjected to the second ball milling treatment to prevent the silicon-based particles from agglomerating and to mix them uniformly with the supercritical graphene to achieve coating.

[0086] In a preferred embodiment, step S2 comprises: contacting the first product with a silicon-containing matrix, ball milling under the fifth ball milling condition, and adding a second organic phase to obtain a fourth ball milling product; subjecting the fourth ball milling product to a second ultrasonic dispersion treatment; after the second ultrasonic dispersion treatment is completed, continuing ball milling under the sixth ball milling condition to obtain a suspension of the second product and subjecting it to the spray drying treatment;

[0087] Optionally, the conditions of the second ultrasonic dispersion treatment include: closed constant temperature ultrasound, ultrasound time of 3 to 8 hours, ultrasound power of 600 to 3000 W, and ultrasound frequency of 20 to 40 KHz; preferably, ultrasound time of 4 to 7 hours, ultrasound power of 600 to 1500 W, and ultrasound frequency of 30 to 40 KHz;

[0088] Optionally, the fifth ball milling condition and the sixth ball milling condition independently include: the ball milling temperature is 23-60°C, the ball milling speed is 50-600rpm, the ball milling time is 0.5-12h, and the ball-to-material ratio is 1-40:1; preferably, the ball milling temperature is 30-50°C, the ball milling speed is 250-400rpm, the ball milling time is 2-6h, and the ball-to-material ratio is 5-20:1.

[0089] In one embodiment, in step S3, the conditions of the spray drying treatment include: a feed temperature of 120 to 200°C; an outlet temperature of 80 to 100°C; a carrier gas flow rate of 12 to 20 L / min, an inlet pressure of 0.3 to 0.8 MPa, and the carrier gas is selected from one or more of nitrogen and argon.

[0090] In a preferred embodiment, in step S3, the feed temperature is 140-190°C; the outlet temperature is 90-100°C; the carrier gas flow rate is 14-18 L / min, and the inlet pressure is 0.4-0.6 MPa. The spray drying device in the present disclosure is a conventional device in the art.

[0091] In one embodiment, in step S4, the conditions for the calcination treatment include:

[0092] In an inert gas atmosphere, first raise the temperature to 270-700°C, and then keep it warm for 1-12 hours; preferably, first raise the temperature to 500-700°C, and then keep it warm for 3-6 hours;

[0093] Preferably, the heating rate is 0.5 to 5°C / min, preferably 0.5 to 3°C / min;

[0094] Optionally, the inert atmosphere is selected from one or more of nitrogen and argon.

[0095] In a preferred embodiment, the method further comprises: using the product obtained by the calcination treatment as the silicon-containing matrix, repeating steps S2 to S4 to obtain a calcined product having multiple carbon coating layers; preferably, the steps are repeated 2 to 3 times. Through multiple coating treatments, multiple carbon coating layers can be formed on the surface of the silicon-containing matrix, which is beneficial to controlling the thickness of the carbon coating layer of the silicon-carbon negative electrode material.

[0096] A second aspect of the present disclosure provides a silicon-carbon negative electrode material prepared according to the method described in the first aspect of the present disclosure.

[0097] In one embodiment, the silicon-carbon negative electrode material includes a silicon-containing matrix and a carbon coating layer, and the carbon coating layer contains graphene; based on the total weight of the silicon-carbon negative electrode material, the content of the silicon-containing matrix is ​​50 to 95 weight%, and the content of the carbon coating layer is 4 to 49 weight%.

[0098] In a preferred embodiment, based on the total weight of the silicon-carbon negative electrode material, the content of the silicon-containing matrix is ​​80-95% by weight, and the content of the carbon coating layer is 5-20% by weight; preferably, the heteroatom content in the silicon-carbon negative electrode material is less than 1% by weight, and the heteroatom includes sulfur, nitrogen and oxygen. The silicon-carbon negative electrode material disclosed in the present invention contains almost no heteroatoms, thereby avoiding the influence of heteroatoms on the conductive properties of the material.

[0099] In one embodiment, the silicon-carbon negative electrode material includes at least one layer of the carbon coating layer; preferably includes 2 to 3 layers.

[0100] In one embodiment, the total thickness of the carbon coating layer is 0.01 to 2 μm, preferably 0.05 to 1 μm.

[0101] In a specific embodiment, the carbon coating layer and the silicon-carbon negative electrode material D 50 The particle size is 2-28 μm, the average pore size is 2-50 nm, and the BET specific surface area is 1-50 m 2 / g, total pore volume is 0.001~0.5cm 3 / g; Preferably, the D of the silicon-carbon negative electrode material 50 The particle size is 4-18 μm, the average pore size is 2-35 nm, and the BET specific surface area is 1-10 m 2 / g, total pore volume is 0.001~0.1cm 3 / g.

[0102] A third aspect of the present disclosure provides a negative electrode plate, comprising the silicon-carbon negative electrode material described in the second aspect of the present disclosure.

[0103] In a specific embodiment, the negative electrode plate is prepared by a method comprising the following steps:

[0104] The silicon-carbon negative electrode material is made into a negative electrode slurry, which is then coated on the surface of a negative electrode current collector and dried to obtain a negative electrode sheet.

[0105] In a specific embodiment, the negative electrode slurry includes the silicon-carbon negative electrode material, a conductive agent, a thickener, a binder and water; based on the total weight of solids in the negative electrode slurry, the content of the silicon-carbon negative electrode material is 80-96 weight%, the content of the conductive agent is 0.01-5 weight%, the content of the thickener is 1-10 weight%, and the content of the binder is 1-10 weight%. The weight ratio of the total weight of solids in the negative electrode slurry to water is 2-0.5:1.

[0106] In a specific embodiment, the conductive agent is selected from one or more of conductive carbon black (super-p, super-p-Li), acetylene black, Ketjen black, single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon nanofibers;

[0107] The thickener is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium alginate, aqueous polyurethane, polyvinyl alcohol, chitosan and β-cyclodextrin;

[0108] The binder is selected from one or more of styrene butadiene copolymer (styrene butadiene rubber), polyacrylic acid, sodium polyacrylate, polyimide, polyvinylidene fluoride, nitrile rubber, butadiene rubber, xanthan gum and gum arabic.

[0109] In a specific embodiment, the negative electrode slurry is made into a negative electrode sheet by the following method: (1) first weigh 80 to 97 parts by weight of silicon-carbon negative electrode material and 1 to 10 parts by weight of Super P-Li (super dense high conductive carbon black) for mechanical mixing; (2) then weigh 1 to 5 parts by weight of CMC (carboxymethyl cellulose) solution with a mass fraction of 1 to 3% by weight and add it to the powder, and mix it in a homogenizer at a speed of 700 to 3000 rpm for 5 to 30 minutes, during which the slurry on the wall is scraped off, stirred and mixed again, and deionized water is added twice in total of 100 parts by weight. (3) After mixing evenly, add 1 to 5 parts by weight of SBR emulsion (styrene butadiene emulsion) with a mass fraction of 10% by weight, and continue to mix in the homogenizer at a speed of 700 to 3000 rpm for 5 to 30 minutes. (4) After the slurry is mixed evenly, observe the fluidity, and the slurry can flow and not stratify when the bottle is tilted. (5) Apply the negative electrode slurry to the current collector copper foil, dry and roll-press to obtain the negative electrode sheet. The final sheet single surface density is 4 mg / cm 2 ~12mg / cm 2 , compacted density 1.10g / cm 3 ~1.80g / cm 3 .

[0110] A fourth aspect of the present disclosure provides a lithium-ion battery, which includes a positive electrode plate, a negative electrode plate as described in the third aspect of the present disclosure, a battery separator, and an electrolyte.

[0111] In a specific embodiment, the positive electrode, electrolyte and separator can be various materials conventionally applicable in the art, and the present disclosure has no particular limitation on this. For example, the separator can be selected from any one of polyethylene film, polypropylene film and cellulose film, the positive electrode plate can be selected from lithium iron phosphate, lithium cobalt oxide, and ternary positive electrode, and the electrolyte can be lithium hexafluorophosphate dissolved in a carbonate mixed solvent.

[0112] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can all be obtained through commercial sources.

[0113] The nitrogen adsorption-desorption curve, average pore size, BET specific surface area and total pore volume of the samples were measured by the JW-BK200 series static volumetric method.

[0114] The SEM test method is scanning electron microscope, and the instrument model is S4800 of Hitachi, Japan;

[0115] The TEM test method is transmission electron microscopy, and the instrument model is Tecnai G2F20 from FEI Company, USA;

[0116] The test method for electrochemical cycle performance is the blue electric test system, and the instrument model is CT3001A.

[0117] The supercritically exfoliated graphene in the present disclosure is prepared by the following method: at a temperature of 40°C and a high pressure (8MPa), using CO 2 The gas is used as a gaseous intercalation medium in a supercritical state, and the graphite sheets are exfoliated in a reactor, and the exfoliated powder is collected to obtain a supercritical exfoliated graphene material. 80% (number percentage) of the supercritical exfoliated graphene prepared by the above method has 1 to 10 layers; the heteroatom content of the supercritical exfoliated graphene is less than 1%; and the plane size of the graphene sheet is in the range of 2 to 10 μm.

[0118] Example 1

[0119] (1) Take 2 g of supercritically exfoliated graphene and disperse it in 200 mL of nitrogen methyl pyrrolidone (first organic phase) at a mixing ratio of 100 ml of the first organic phase / 1 g of graphene. Mix them evenly and then put them in a ball mill at room temperature at a speed of 400 rpm for 2 h. The ball-to-material ratio is 20:1.

[0120] (2) Add 0.2 g of sodium dodecylbenzene sulfonate (surfactant) into the dispersed suspension and continue ball milling for 2 h.

[0121] (3) Add poly(vinylidene fluoride) (polymer material with an average molecular weight of 4×10 5 , Macklin) 0.2g, and continue ball milling for 2h to obtain the first product; wherein the weight ratio of the surfactant to the polymer material is 1:1, and the weight ratio of graphene to the total weight of the surface modification additive is 1:0.2.

[0122] (4) Then, a first ultrasonic dispersion treatment is performed. The conditions of the first ultrasonic dispersion treatment include: closed constant temperature ultrasound (normal temperature), ultrasonic time of 6 hours, ultrasonic power of 600 W, and ultrasonic frequency of 40 KHz. After the first ultrasonic treatment is completed, ball milling is continued for 2 hours.

[0123] (5) Add 10 g of silicon dioxide SiO particles (particle size 2 μm, purchased from Adamas) (the weight ratio of silicon dioxide to supercritically exfoliated graphene is 5:1), adjust the rotation speed to 300 rpm, and continue ball milling at room temperature for 4 h, with a ball-to-material ratio of 20:1. During the ball milling process, continue to add 100 ml of nitrogen methyl pyrrolidone (second organic phase), and the amount of the second organic phase is 50 ml relative to 1 g of the solid of the first product.

[0124] (6) The suspension liquid was spray dried. The spray drying conditions were: inlet temperature 180°C, outlet temperature 90°C, feed rate 10 ml / min, carrier gas was nitrogen, carrier gas flow rate was 15 L / min, and inlet pressure was 0.5 MPa.

[0125] (7) The dried powder was placed in an atmosphere furnace for calcination and carbonization. The calcination conditions were: in an Ar atmosphere, the temperature was raised to 500°C at 3°C / min, and then the temperature was kept for 4 hours to obtain a negative electrode material, which was recorded as F-1.

[0126] Figure 1 is a scanning electron microscope (SEM) image of the supercritical graphene used in the preparation process of this embodiment. Figure 1 It can be seen that the supercritically exfoliated graphene is a thin layer of graphene with about 8 layers. Figure 1 The graphene contains sheet-like folds, and the size after folding is 2μm.

[0127] Figure 2 The nitrogen adsorption-desorption curve of the supercritically exfoliated graphene used in the preparation process of this embodiment is shown in the BET specific surface area test report, which shows that the multi-point BET specific surface area of ​​the graphene is 7.64 m 2 / g, indicating that the supercritically exfoliated graphene structure is relatively complete, without a large number of porous structures, and can be used as a better coating material.

[0128] Example 2

[0129] This example refers to the preparation method in Example 1, and the difference from Example 1 is that the silicon-containing matrix silicon oxide is replaced with nano-silicon particles of the same mass (the D of the nano-silicon particles is 50 The particle size is 80 nm), and the rest of the process is the same as in Example 1 to obtain a negative electrode material, which is recorded as F-2.

[0130] Example 3

[0131] In this embodiment, the negative electrode material is prepared by referring to the method of embodiment 1, and the difference from embodiment 1 is that the coating is repeated twice, and the specific process includes: a. the dispersion obtained in step (3) of embodiment 1 is divided into two parts, one of which is prepared into the negative electrode material F-1' according to the steps (4) to (6) of embodiment 1; b. the negative electrode material F-1' is added to the other dispersion, and the ball milling, drying and carbonization are performed again according to the conditions of (4) to (6) to obtain the negative electrode material, which is recorded as F-3.

[0132] Example 4

[0133] This embodiment refers to the preparation method of embodiment 1, and the difference from embodiment 1 is that the silicon-containing matrix silicon oxide is replaced by nano silicon-metal aluminum alloy particles (particles D 50 The particle size is 700nm), based on the total weight of the nano-silicon-metal aluminum alloy, the silicon content is 50% by weight, and the rest of the process is the same as in Example 1 to obtain a negative electrode material, which is recorded as F-4.

[0134] Example 5

[0135] (1) Take 1 g of supercritically exfoliated graphene and disperse it in 200 mL of anhydrous ethanol (first organic phase) at a mixing ratio of 50 ml of the first organic phase / 1 g of graphene. Mix them evenly and then mill them in a ball mill at room temperature at a speed of 300 rpm for 2 h. The ball-to-material ratio is 5:1.

[0136] (2) Add 0.1 g of sodium dodecylbenzene sulfonate (surfactant) into the dispersed suspension and continue ball milling for 2 h.

[0137] (3) Add poly(vinylidene fluoride) (polymer material with an average molecular weight of 4×10 5 , Macklin) 0.2g, and continue ball milling for 2h to obtain the first product; wherein the weight ratio of the surfactant to the polymer material is 0.5:1, and the weight ratio of the total weight of the surface modification additive to the graphene is 0.3:1.

[0138] (4) Then, a first ultrasonic dispersion treatment is performed. The conditions of the first ultrasonic dispersion treatment include: closed constant temperature ultrasound (normal temperature), ultrasonic time of 6 hours, ultrasonic power of 600 W, and ultrasonic frequency of 40 KHz. After the first ultrasonic treatment is completed, ball milling is continued for 2 hours.

[0139] (5) Add 10 g of silicon dioxide SiO particles (particle size 500 nm, purchased from Adamas) (the weight ratio of silicon dioxide to supercritically exfoliated graphene is 10:1), adjust the rotation speed to 300 rpm, and continue ball milling at room temperature for 4 h, with a ball-to-material ratio of 5:1. During the ball milling process, continue to add 100 ml of ethanol (second organic phase). The amount of the second organic phase is 100 ml relative to 1 g of the first product solid;

[0140] (6) The suspension liquid was spray dried. The spray drying conditions were: inlet temperature 180°C, outlet temperature 90°C, feed rate 10 ml / min, carrier gas was nitrogen gas, carrier gas flow rate was 15 L / min, and inlet pressure was 0.5 MPa.

[0141] (7) The dried powder was placed in an atmosphere furnace for calcination and carbonization. The calcination conditions were: in an Ar atmosphere, the temperature was raised to 700°C at 3°C / min and then kept at this temperature for 4 hours to obtain a negative electrode material, which was recorded as F-5.

[0142] Example 6

[0143] This embodiment refers to the preparation method of Example 1, and the difference from Example 1 is that the surfactant is replaced by stearic acid, and the polymer material is replaced by polycarbonate (average molecular weight is about 45,000, Macklin). The rest of the process is the same as Example 1 to obtain a negative electrode material, which is recorded as F-6.

[0144] Example 7

[0145] This embodiment refers to the preparation method of embodiment 1, and the difference from embodiment 1 is that the calcination conditions in step (6) are adjusted to: in an Ar atmosphere, the temperature is raised to 1000°C at 2°C / min, and the heat preservation time is 3h to obtain a negative electrode material, which is recorded as F-7.

[0146] Example 8

[0147] (1) Take 2 g of supercritically exfoliated graphene and disperse it in 200 mL of nitrogen methyl pyrrolidone (first organic phase) at a mixing ratio of 100 ml of the first organic phase / 1 g of graphene. Mix them evenly and then put them in a ball mill at room temperature at a speed of 400 rpm for 2 h. The ball-to-material ratio is 20:1.

[0148] (2) Add 0.2 g of sodium dodecylbenzene sulfonate (surfactant) into the dispersed suspension and continue ball milling for 2 h.

[0149] (3) Add poly(vinylidene fluoride) (polymer material with an average molecular weight of 4×10 5 , Macklin) 0.2g, and continue ball milling for 2h, wherein the weight ratio of the surfactant to the polymer material is 1:1, and the weight ratio of graphene to the total weight of the surface modification additive is 1:0.2.

[0150] (4) Then, a first ultrasonic dispersion treatment is performed. The conditions of the first ultrasonic dispersion treatment include: closed constant temperature ultrasound (normal temperature), ultrasonic time of 6 hours, ultrasonic power of 800 W, and ultrasonic frequency of 40 KHz. After the first ultrasonic treatment is completed, ball milling is continued for 2 hours.

[0151] (5) Add 10 g of silicon dioxide SiO particles (particle size 2 μm, purchased from Adamas) (the weight ratio of silicon dioxide to supercritically exfoliated graphene is 5:1), adjust the rotation speed to 300 rpm, and continue ball milling at room temperature for 2 h, with a ball-to-material ratio of 20:1. Continue to add 100 ml of nitrogen methyl pyrrolidone (second organic phase) during the ball milling process. The amount of the second organic phase is 50 ml relative to 1 g of the first product solid, and then perform a second ultrasonic dispersion treatment; the conditions of the second ultrasonic dispersion treatment include: closed constant temperature ultrasound, ultrasonic time of 4 h, ultrasonic power of 600 W, ultrasonic frequency of 40 KHz, and continue ball milling for 2 h after the second ultrasonic dispersion treatment is completed.

[0152] (6) The suspension liquid was spray dried. The spray drying conditions were: inlet temperature 180°C, outlet temperature 90°C, feed rate 10 ml / min, carrier gas was nitrogen, carrier gas flow rate was 15 L / min, and inlet pressure was 0.5 MPa.

[0153] (7) The dried powder was placed in an atmosphere furnace for calcination and carbonization. The calcination conditions were: in an Ar atmosphere, the temperature was raised to 500°C at 3°C / min and then kept at this temperature for 4 hours to obtain a negative electrode material, which was recorded as F-8.

[0154] Example 9

[0155] This example refers to the preparation method in Example 1, and the difference from Example 1 is that the addition ratio of the materials is changed, specifically including:

[0156] In step (1), 2 g of supercritically exfoliated graphene is dispersed in 400 mL of nitrogen methyl pyrrolidone (first organic phase). The amount of the first organic phase is 200 ml relative to 1 g of graphene.

[0157] In step (2), 0.53 g of sodium dodecylbenzene sulfonate (surfactant) is first added to the dispersed suspension.

[0158] In step (3), poly(vinylidene fluoride) (polymer material, average molecular weight 4×10 5 , Macklin) 0.27g; wherein the weight ratio of the surfactant to the polymer material is 2:1, and the weight ratio of the graphene to the total weight of the surface modification additive is 1:0.4.

[0159] In step (5), 7.5 g of silicon dioxide SiO particles (particle size 2 μm, purchased from Adamas) were added (the weight ratio of silicon dioxide to supercritically exfoliated graphene was 3.75:1). During the ball milling process, 80 ml of nitrogen methyl pyrrolidone (second organic phase) was added. The amount of the second organic phase was 29 ml relative to 1 g of the first product solid. The rest of the process was the same as in Example 1 to obtain a negative electrode material, which was recorded as F-9.

[0160] Example 10

[0161] This example refers to the preparation method in Example 1, and the difference from Example 1 is that the addition ratio of the materials is changed, specifically including:

[0162] In step (1), 2 g of supercritically exfoliated graphene is dispersed in 600 mL of nitrogen methyl pyrrolidone (first organic phase). The amount of the first organic phase is 300 ml relative to 1 g of graphene.

[0163] In step (2), 0.01 g of sodium dodecylbenzene sulfonate (surfactant) is first added to the dispersed suspension.

[0164] In step (3), poly(vinylidene fluoride) (polymer material, average molecular weight 4×10 5 , Macklin) 0.2g; wherein the weight ratio of the surfactant to the polymer material is 1:20, and the weight ratio of the graphene to the total weight of the surface modification additive is 1:0.105.

[0165] In step (5), 50 g of silicon dioxide SiO particles (particle size 2 μm, purchased from Adamas) were added (the weight ratio of silicon dioxide to supercritically exfoliated graphene was 25:1). During the ball milling process, 300 ml of nitrogen methyl pyrrolidone (second organic phase) was added. The amount of the second organic phase was 6 ml relative to 1 g of the first product solid. The rest of the process was the same as in Example 1 to obtain a negative electrode material, which was recorded as F-10.

[0166] Embodiment 11

[0167] This example refers to the preparation method in Example 1, and the difference from Example 1 is that the processing conditions are changed, specifically including:

[0168] In step (1), the supercritically exfoliated graphene is dispersed in nitrogen methyl pyrrolidone (the first organic phase), mixed evenly, and then milled in a ball mill at room temperature at a speed of 200 rpm for 4 hours, with a ball-to-material ratio of 40:1.

[0169] In step (2), sodium dodecylbenzene sulfonate (surfactant) is first added to the dispersed suspension, and then ball milling is continued for 4 hours.

[0170] In step (3), after adding poly(vinylidene fluoride), ball milling is continued for 4 hours to obtain the first product.

[0171] In step (5), after adding silicon dioxide SiO particles, the rotation speed is adjusted to 100 rpm, and ball milling is continued for 12 hours at room temperature, with a ball-to-material ratio of 40:1.

[0172] In step (6), the suspension liquid is spray dried, and the spray drying conditions are: inlet temperature 120°C, outlet temperature 80°C, feed rate 10ml / min, carrier is nitrogen, carrier gas flow rate is 12L / min, and inlet pressure is 0.8MPa.

[0173] In step (7), the dried powder is placed in an atmosphere furnace for calcination and carbonization. The calcination conditions are: in an Ar atmosphere, the temperature is raised to 270°C at 5°C / min, and then the heat preservation time is 12h to obtain a negative electrode material, which is recorded as F-11.

[0174] Example 12

[0175] This example refers to the preparation method in Example 1, and the difference from Example 1 is that the processing conditions are changed, specifically including:

[0176] In step (1), the supercritically exfoliated graphene is dispersed in nitrogen methyl pyrrolidone (the first organic phase), mixed evenly, and then milled in a ball mill at room temperature at a rotation speed of 1500 rpm for 5 hours, with a ball-to-material ratio of 50:1.

[0177] In step (2), sodium dodecylbenzene sulfonate (surfactant) is first added to the dispersed suspension, and then ball milling is continued for 5 hours.

[0178] In step (3), after adding poly(vinylidene fluoride), ball milling is continued for 5 hours to obtain the first product.

[0179] In step (5), after adding silicon dioxide SiO particles, the rotation speed is adjusted to 800 rpm, and ball milling is continued for 15 hours at room temperature, with a ball-to-material ratio of 50:1.

[0180] In step (6), the suspension liquid is spray dried, and the spray drying conditions are: inlet temperature 250°C, outlet temperature 120°C, feed rate 10ml / min, carrier is nitrogen, carrier gas flow rate is 8L / min, and inlet pressure is 0.1MPa.

[0181] In step (7), the dried powder is placed in an atmosphere furnace for calcination and carbonization. The calcination conditions are: in an Ar atmosphere, the temperature is raised to 800°C at 10°C / min, and then the heat preservation time is 0.5h to obtain a negative electrode material, which is recorded as F-12.

[0182] Comparative Example 1

[0183] This comparative example prepares the negative electrode material by referring to the method of Example 1, and the difference from Example 1 is that:

[0184] The nitrogen methyl pyrrolidone (the first organic phase and the second organic phase) added in step (1) and step (5) was replaced with deionized water, respectively. The rest of the process was the same as in Example 1 to prepare a negative electrode material, which was recorded as D-1.

[0185] Comparative Example 2

[0186] In this comparative example, the negative electrode material is prepared according to the method of Example 2, which is different from Example 2 in that: in step (1), graphene prepared by supercritical exfoliation is not added, and the rest of the process is the same as Example 2 to prepare a negative electrode material, which is recorded as D-2.

[0187] Comparative Example 3

[0188] In this comparative example, the negative electrode material was prepared by referring to the method of Example 1, except that step (7) of low temperature carbonization was not performed. The rest of the process was the same as that of Example 1, and a negative electrode material was prepared, which was recorded as D-3.

[0189] Comparative Example 4

[0190] In this comparative example, the negative electrode material was prepared by referring to the method of Example 1, except that the graphene prepared by supercritical exfoliation was replaced by graphene oxide, and the rest of the process was the same as that of Example 1 to prepare the negative electrode material, which was recorded as D-4.

[0191] Comparative Example 5

[0192] In this comparative example, the negative electrode material is prepared by referring to the method of Example 1, which is different from Example 1 in that the graphene prepared by supercritical exfoliation is replaced by carbon nanotubes, and the rest of the process is the same as Example 1 to prepare the negative electrode material, which is recorded as D-5.

[0193] Comparative Example 6

[0194] This comparative example refers to the method of preparing the negative electrode material in Example 1, which is different from Example 1 in that no surfactant (sodium dodecylbenzene sulfonate) and polymer material (poly(vinylidene fluoride)) are added, that is, steps (2) to (3) are not performed, and the remaining process is the same as in Example 1 to prepare a negative electrode material, which is recorded as D-6.

[0195] The test data of component contents and structural parameters of the negative electrode material products prepared in the above examples and comparative examples are listed in the following Table 1.

[0196] Table 1

[0197]

[0198]

[0199] Test Example 1

[0200] This test example is used to illustrate the electrochemical performance of the products obtained in the examples and comparative examples when used as negative electrode materials for lithium-ion batteries.

[0201] The products obtained in the examples and comparative examples were used as negative electrodes to assemble lithium-ion batteries, and their electrochemical properties were tested. The specific steps are as follows:

[0202] (1) The products obtained in the embodiment and the comparative example were respectively mixed in a vacuum homogenizer with Super P-Li material (conductive agent), CMC (thickener, carboxymethyl cellulose), and SBR (binder, styrene butadiene copolymer) in a mass ratio of 92:2:2:3, and deionized water was added to adjust the viscosity for 30 minutes to obtain a negative electrode slurry. Based on the total weight of solids in the negative electrode slurry, the content of silicon-carbon negative electrode material was 92 weight%, the content of conductive agent was 2 weight%, the content of thickener was 2 weight%, and the content of binder was 3 weight%; the weight ratio of the total weight of solids in the negative electrode slurry to water was 0.8:1; then coated on a copper current collector, the coating thickness after dry roller pressing was 45 μm, and dried in a vacuum oven at 120° C. for 8 hours to obtain a negative electrode sheet.

[0203] (2) The prepared negative electrode sheet is used as the positive electrode of the battery, the metal lithium sheet is used as the negative electrode, and the Celgard 2325 type diaphragm and 1 mol / L LiPF 6 The electrolyte solution (volume ratio of solvent is ethylene carbonate: dimethyl carbonate: diethyl carbonate = 1:1:1) and the additive is FEC (fluoroethylene carbonate) in an amount of 5 vol % were assembled into a button half-cell in a glove box.

[0204] The battery was charged and discharged using the Blue Electric system. The parameters were set as follows: current density was 0.1C for the first cycle, followed by a change in rate, and voltage range was 0.005 to 1.5V. The test results are listed in Table 2 below.

[0205] Table 2

[0206]

[0207]

[0208] From the data in Table 2 above, we can see that:

[0209] (1) By comparing Example 1 with Comparative Example 1, it can be seen that Comparative Example 1 uses supercritical graphene and SiO silicon-based particles dispersed in water without using an organic phase, and the discharge specific capacity of the material will quickly decay from 1716.5mAh / g (Example 1) to 372.1mAh / g (Comparative Example 1), and the first coulombic efficiency decays from 62.5% in Example 1 to 24.1% in Comparative Example 1, indicating that the method provided by the present disclosure, adding the first organic phase and the second organic phase during the ball milling process, can avoid the reaction of silicon particles with the liquid phase, and effectively improve the discharge specific capacity, first coulombic efficiency and cycle efficiency of the negative electrode material. By comparing Example 1 with Comparative Example 3, it can be seen that the first coulombic efficiency and cycle performance of the negative electrode material prepared by low-temperature carbonization in Example 1 are higher than those of the negative electrode material obtained by Comparative Example 1 without low-temperature carbonization, especially the cycle performance has been significantly improved. By comparing Example 2 with Comparative Example 2, it can be seen that in Example 2, nano-silicon is coated with supercritical exfoliated graphene. Compared with Comparative Example 2 without adding supercritical exfoliated graphene, the cycle performance of the negative electrode material obtained in Example 2 is significantly improved, and the capacity retention rate after 50 cycles is increased from 62.9% in Comparative Example 2 to 86.8% in Example 2. By comparing Example 1 with Comparative Examples 4 to 6, it can be seen that the first coulombic efficiency and cycle capacity retention rate of the negative electrode material prepared according to the method provided in the present disclosure in Example 1 are improved.

[0210] (2) By comparing Example 1 with Example 3, it can be seen that the effect of double coating of SiO2 by the method provided by the present disclosure in Example 3 is better than the single coating effect in Example 1. The first coulombic efficiency is increased from 62.5% to 70.6%, and the capacity retention rate after 50 cycles is increased from 68.2% to 91.7%.

[0211] (3) By comparing Examples 1 and 7, it can be seen that Example 1 adopts a low-temperature carbonization of 500°C, and Example 7 adopts a high-temperature carbonization of 1000°C. Compared with the negative electrode material obtained in Example 7, the first coulombic efficiency and cycle capacity retention rate of the negative electrode material obtained in Example 1 are improved.

[0212] (4) By comparing Example 1 with Example 8, it can be seen that Example 8 adds a second ultrasonic dispersion step during the preparation process, and the first coulombic efficiency and cycle capacity retention rate of the negative electrode material obtained in Example 8 are improved.

[0213] (5) By comparing Example 1 with Example 9 and Example 11, it can be seen that Example 9 did not prepare the negative electrode material according to the optimized addition ratio provided in the present disclosure, and Example 11 did not prepare the negative electrode material according to the optimized preparation conditions provided in the present disclosure. Compared with Example 9 and Example 11, the negative electrode material prepared in Example 1 has higher first coulombic efficiency and cycle capacity retention rate.

[0214] Test Example 2

[0215] This test example is used to illustrate the conductivity of the negative electrode materials prepared in the embodiments and comparative examples of the present disclosure. The test instrument and test method include: using Ningbo Ruike FT-301 multifunctional powder resistivity tester to test the conductivity of the powder negative electrode material under a pressure of 25 MPa. The test results are listed in Table 3 below.

[0216] Table 3

[0217]

[0218]

[0219] It can be seen from the data in Table 3 above that the negative electrode material prepared according to the method provided in the present disclosure can have a higher electrical conductivity.

[0220] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0221] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0222] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: S1, contacting the supercritically exfoliated graphene and the surface modification additive with a first organic phase, and performing a first ball milling treatment to obtain a first product, wherein the surface modification additive is selected from one or more of a surfactant and a polymer material; S2, contacting the first product, the silicon-containing matrix and a second organic phase, and performing a second ball milling treatment to obtain a second product; S3, spray drying the second product to obtain a third product; S4, calcining the third product.

2. The method according to claim 1, characterized in that In step S1, the weight ratio of the graphene to the surface modification additive is 1:0.01-0.5, preferably 1:0.01-0.3; preferably, in the surface modification additive, the weight ratio of the surfactant to the polymer material is 0.1-10:1, preferably 0.1-1:1; Optionally, in step S1, the planar size of the supercritically exfoliated graphene is in the range of 2 to 10 μm; preferably, based on the total weight of the supercritically exfoliated graphene, more than 80% by weight of the supercritically exfoliated graphene has less than 10 layers; the heteroatom content of the supercritically exfoliated graphene is less than 1% by weight, and the heteroatom is selected from one or more of oxygen, nitrogen and sulfur; Optionally, the supercritically exfoliated graphene is prepared by a method comprising the following steps: At a temperature of 32°C to 150°C and a pressure of more than 4MPa, a gaseous intercalation medium is used to exfoliate graphite sheets in a reaction vessel under a supercritical state, and the exfoliated powder is collected to obtain supercritically exfoliated graphene; optionally, the gaseous intercalation medium is selected from one or both of carbon dioxide and nitrogen; optionally, the reaction vessel is a stirred tank or a reactor.

3. The method according to claim 1, characterized in that The surfactant is selected from one or more of sodium lignin sulfonate, sodium methylene dibenzene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, polyol esters, fatty acid glycerides, oleic acid, oleylamine, oleamide, stearic acid, polysorbate-80, polyethylene glycol octylphenyl ether and cetyltrimethylammonium bromide; preferably, the surfactant is selected from one or more of sodium lignin sulfonate, polyol esters, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, oleamide and stearic acid; The polymer material is selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyacrylic acid, polyurethane, polyphenylene sulfide, polystyrene butadiene copolymer, epoxy resin, acrylonitrile butadiene styrene, polyvinyl pyrrolidone, polycarbonate and polyamide; preferably, the polymer material is selected from one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, polyacrylic acid, polystyrene butadiene copolymer and polyamide; optionally, the molecular weight of the polymer material is (0.01-20)×10 5 ; Optionally, the first organic phase is selected from one or more of nitrogen methyl pyrrolidone, ethanol, isopropanol, cyclohexane, petroleum ether, furfural, tetrahydrofuran, high aromatic oil and paraffin mineral oil; Preferably, the amount of the first organic phase used is 10 to 200 ml, preferably 50 to 100 ml, relative to 1 g of graphene.

4. The method according to claim 1, characterized in that: In step S1, the conditions of the first ball milling treatment include: a ball milling temperature of 23 to 60°C, a ball milling speed of 200 to 1000 rpm, a ball milling time of 0.5 to 12 hours, and a ball-to-material ratio of 1 to 40:1; preferably, the ball milling temperature is 30 to 50°C, the ball milling speed is 300 to 800 rpm, the ball milling time is 2 to 6 hours, and the ball-to-material ratio is 5 to 20:

1.

5. The method according to claim 1, characterized in that Step S1 includes: Disperse the graphene in a first organic phase and ball-mill under first ball-milling conditions to obtain a first ball-milled product; then contact the first ball-milled product with the surfactant and continue ball-milling under second ball-milling conditions to obtain a second ball-milled product; contact the second ball-milled product with a polymer material and continue ball-milling under third ball-milling conditions to obtain a third ball-milled product; after subjecting the third ball-milled product to a first ultrasonic dispersion treatment, continue ball-milling under fourth ball-milling conditions to obtain the first product; Optionally, the conditions of the first ultrasonic dispersion treatment include: sealed and constant-temperature ultrasonic treatment, with an ultrasonic time of 3 to 8 h, an ultrasonic power of 600 to 3000 W, and an ultrasonic frequency of 20 to 40 KHz; preferably, the ultrasonic time is 3 to 7 h, the ultrasonic power is 600 to 1500 W, and the ultrasonic frequency is 30 to 40 KHz; Optionally, the first ball-milling conditions, the second ball-milling conditions, the third ball-milling conditions, and the fourth ball-milling conditions each independently include: a ball-milling temperature of 23 to 60 °C, a ball-milling speed of 200 to 1000 rpm, a ball-milling time of 0.5 to 12 h, and a ball-to-material ratio of 1 to 40:1; preferably, the ball-milling temperature is 30 to 50 °C, the ball-milling speed is 300 to 800 rpm, the ball-milling time is 2 to 6 h, and the ball-to-material ratio is 5 to 20:

1.

6. The method according to claim 1, characterized in that In step S2, the silicon-containing matrix is selected from one or more of nano-silicon, SiOx, and nano-silicon-metal M alloy, where 0.3 < x < 1.6, and M is selected from one or more of aluminum, iron, copper, titanium, niobium, chromium, lithium, manganese, nickel, cobalt, tin, vanadium, germanium, magnesium, calcium, molybdenum, and lanthanum. Optionally, based on the total weight of the nano-silicon-metal M alloy, the silicon content is 70 to 99 wt%, preferably 80 to 98 wt%; Preferably, the weight ratio of the silicon-containing matrix to the supercritically exfoliated graphene is 1 to 20:1, preferably 5 to 20:1; Optionally, the second organic phase is selected from one or more of N-methylpyrrolidone, ethanol, isopropanol, cyclohexane, petroleum ether, furfural, tetrahydrofuran, high-aromatic hydrocarbon oil, and paraffin mineral oil; Preferably, with respect to 1 g of the solid of the first product, the amount of the second organic phase used is 10 to 200 ml, preferably 50 to 100 ml.

7. The method according to claim 1, characterized in that In step S2, the conditions of the second ball-milling treatment include: a ball-milling temperature of 23 to 60 °C, a ball-milling speed of 50 to 600 rpm, a ball-milling time of 0.5 to 12 h, and a ball-to-material ratio of 1 to 40:1; preferably, the ball-milling temperature is 30 to 50 °C, the ball-milling speed is 250 to 400 rpm, the ball-milling time is 2 to 6 h, and the ball-to-material ratio is 5 to 20:

1.

8. The method according to claim 1, characterized in that Step S2 includes: Contact the first product with a silicon-containing matrix, ball-mill under fifth ball-milling conditions, and add a second organic phase to obtain a fourth ball-milled product; subject the fourth ball-milled product to a second ultrasonic dispersion treatment; after the second ultrasonic dispersion treatment is completed, continue ball-milling under sixth ball-milling conditions to obtain a suspension of the second product for the spray drying treatment; Optionally, the conditions of the second ultrasonic dispersion treatment include: closed constant temperature ultrasound, ultrasound time of 3 to 8 hours, ultrasound power of 600 to 3000 W, and ultrasound frequency of 20 to 40 KHz; preferably, ultrasound time of 4 to 7 hours, ultrasound power of 600 to 1500 W, and ultrasound frequency of 30 to 40 KHz; Optionally, the fifth ball milling condition and the sixth ball milling condition independently include: the ball milling temperature is 23-60°C, the ball milling speed is 50-600rpm, the ball milling time is 0.5-12h, and the ball-to-material ratio is 1-40:1; preferably, the ball milling temperature is 30-50°C, the ball milling speed is 250-400rpm, the ball milling time is 2-6h, and the ball-to-material ratio is 5-20:

1.

9. The method according to claim 1, characterized in that: In step S3, the conditions of the spray drying treatment include: a feed temperature of 120 to 200°C, an outlet temperature of 80 to 100°C, a carrier gas flow rate of 12 to 20 L / min, an inlet pressure of 0.3 to 0.8 MPa, and the carrier gas is selected from one or more of nitrogen and argon; preferably, the feed temperature is 140 to 190°C, the outlet temperature is 90 to 100°C, the carrier gas flow rate is 14 to 18 L / min, and the inlet pressure is 0.4 to 0.6 MPa.

10. The method according to claim 1, characterized in that In step S4, the conditions of the calcination treatment include: in an inert gas atmosphere, first heating to 270-700°C, and then keeping warm for 1-12 hours; preferably, first heating to 500-700°C, and then keeping warm for 3-6 hours; preferably, the heating rate is 0.5-5°C / min, preferably 0.5-3°C / min; Optionally, the inert gas atmosphere is selected from one or more of a nitrogen atmosphere and an argon atmosphere.

11. The method according to claim 1, characterized in that: The method further comprises: using the product obtained by the calcination treatment as the silicon-containing matrix, and repeating steps S2 to S4 to obtain a calcined product having a plurality of carbon coating layers; preferably, the steps are repeated 2 to 3 times.

12. The silicon-carbon negative electrode material prepared according to the method according to any one of claims 1 to 11.

13. The silicon-carbon negative electrode material according to claim 12, characterized in that: The silicon-carbon negative electrode material comprises a silicon-containing matrix and a carbon coating layer, wherein the carbon coating layer comprises graphene; optionally, the content of the carbon coating layer is 4 to 49% by weight, preferably 5 to 20% by weight; Optionally, the total thickness of the carbon coating layer is 10 to 200 nm, preferably 50 to 100 nm; Optionally, the D of the silicon-carbon negative electrode material 50 The particle size is 2-28 μm, and the BET specific surface area is 1-50 m 2 / g; Preferably, the D of the silicon-carbon negative electrode material 50 The particle size is 4 to 18 μm, and the BET specific surface area is 1 to 10 m 2 / g.

14. A negative electrode plate, characterized in that: Contains the silicon-carbon negative electrode material described in claim 12 or 13.

15. The negative electrode sheet according to claim 14, characterized in that: The negative electrode plate is prepared by a method comprising the following steps: The silicon-carbon negative electrode material is made into a negative electrode slurry, which is then coated on the surface of the negative electrode current collector, and dried to obtain a negative electrode sheet; Preferably, the negative electrode slurry comprises the silicon-carbon negative electrode material, a conductive agent, a thickener, a binder and water; Further preferably, based on the total weight of solids in the negative electrode slurry, the content of the silicon-carbon negative electrode material is 80-96 weight %, the content of the conductive agent is 0.01-5 weight %, the content of the thickener is 1-10 weight %, and the content of the binder is 1-10 weight %; optionally, the weight ratio of the total weight of solids in the negative electrode slurry to water is 2-0.5:1; Optionally, the conductive agent is selected from one or more of conductive carbon black, acetylene black, Ketjen black, single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon nanofibers; The thickener is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, sodium alginate, aqueous polyurethane, polyvinyl alcohol, chitosan and β-cyclodextrin; The binder is selected from one or more of styrene butadiene copolymer, polyacrylic acid, sodium polyacrylate, polyimide, polyvinylidene fluoride, nitrile rubber, butadiene rubber, xanthan gum and gum arabic.

16. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet as claimed in claim 14 or 15, a battery separator and an electrolyte.

Citation Information

Patent Citations

  • Composite negative electrode material, preparation method thereof and lithium ion battery

    CN111162268A

  • Silicon-based negative electrode material, preparation method thereof and lithium ion secondary battery

    CN111816859A

  • Battery negative electrode active material and preparation method thereof

    CN113611858A

  • Silicon-based negative electrode material and preparation method thereof

    CN113725409A

  • Graphene modified silicon negative electrode material and preparation method and application thereof

    CN114613955A